Climate change impacts on agricultural suitability and yield reduction in a Mediterranean region - Abd-Elmabod, Sameh K.; Muñoz-Rojas, Miriam; Jordán, Antonio; Anaya-Romero, Mariá; Phillips, Jonathan D.; Jones, Laurence; Zhang, Zhenhua; Pereira, Paulo; Fleskens, Luuk; van der Ploeg, Martine; de la Rosa, Diego (Geoderma, 2020)
•We evaluated land suitability and yield reduction under climate change scenarios.•Land suitability declines/changes for some soil types with climate change.•Yield reduction of sunflower will be much greater than for wheat under climate change. Climate change impacts are a serious threat to food provisioning, security and the economy. Thus, assessing agricultural suitability and yield reduction under climate change is crucial for sustainable agricultural production. In this study, we used two sub-models of the agro-ecological decision support system MicroLEIS (Terraza and Cervatana) to evaluate the impacts of climate change on land capability and yield reduction of wheat and sunflower as major rainfed crops in different Mediterranean soil types (in Andalucia, Southern Spain). The Terraza sub-model provides an experimental prediction for the bioclimate deficiency and yield reduction, while the Cervatana sub-model predicts the general land use suitability for specific agricultural uses. Sixty-two districts in Southern Spain were modeled and mapped using soil data and the A1B climate scenario (balanced scenario) for three 30-year periods ending in 2040, 2070 and 2100, respectively. Our results showed that the majority of agricultural soils were suitable for wheat production, and less for sunflowers, especially under projected climate change scenarios. Extreme impacts of climate change were observed in the soil types Typic Xerofluvents and Calcic Haploxerepts, where the land capability was reduced from Good and Moderate classes to the Marginal class. This was especially observed in sunflower crops by 2100. Yield reduction of sunflower was much higher than the reduction for wheat, especially under the projected climate periods, where the results for 2100 showed the severest effect on crop yields with about 95% of the sunflower area showing yield reductions. This high variability of the evaluation results demonstrates the importance of using soil factors, climate and crop information in conjunction in decision-making regarding the formulation of site-specific soil use and management strategies.